2020
DOI: 10.18203/2349-3291.ijcp20202606
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the effect of oral motor intervention protocols on oral motor skills of preterm infants from tertiary care hospital in metropolitan city: pilot study

Abstract: Background: Premature infants often have feeding difficulties leading to morbidity or developmental co-morbidities. Premature infant oral motor intervention (PIOMI), has shown the positive effects on feeding progression of the premature infants. PIOMI with the massage technique, may help in improving oral motor activity, weight gain in preterm infants along with better neurobehavioral organization. The study was done to analyse effect of this combined protocol on achieving oral motor control and Neurobehaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 12 publications
(19 reference statements)
0
9
0
Order By: Relevance
“…Jaywant & Kale (2020) found that adding infant massage to PIOMI decreased time to full oral feedings compared to PIOMI alone (24,25). Chailangka et al (2018) and Le et al (2021) found that adding expressed breastmilk to the NNS step of PIOMI resulted in higher feeding e ciency than PIOMI alone (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jaywant & Kale (2020) found that adding infant massage to PIOMI decreased time to full oral feedings compared to PIOMI alone (24,25). Chailangka et al (2018) and Le et al (2021) found that adding expressed breastmilk to the NNS step of PIOMI resulted in higher feeding e ciency than PIOMI alone (23).…”
Section: Discussionmentioning
confidence: 99%
“…Because the premature infants have little control on oral movement, which is associated with lower muscle tone around the mouth, less sensation, and lower tongue strength, PIOMI was selected as oral stimulation in this study because it designed speci cally for premature infants and has demonstrated overwhelming evidence of effectiveness (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…7,12,24,[27][28][29][30][31][32][33][34][35][36][37][38] which often results in decreased LOS. Other RCTs have shown PIOMI's positive effect on NNS scores, 37 behavioral state, 30 and higher scores on the Infant Neurological International Battery (INFANIB) even sustained at 3 and 6 months after discharge. 26 However, there are no studies that have quantitatively tested PIOMI specifically on sucking capacity using pressure manometry.…”
Section: E197mentioning
confidence: 99%
“…26 However, there are no studies that have quantitatively tested PIOMI specifically on sucking capacity using pressure manometry. In addition, although most oral motor studies include the outcome of weight, results vary with some studies demonstrating increased weight gain with PIOMI 28,30,33 while others have not shown this effect. 26,38 No studies were found that measured PIOMI's effect on head circumference.…”
Section: E197mentioning
confidence: 99%
See 1 more Smart Citation